Analysis on the characteristic of the basic airs of half pipe snowboarding - Zhang, H.-Q.; Guo, S.-P.; Wang, B.-H. (China Winter Sports, 2008)
In half pipe snowboarding competition, the judges must remember the names and characters of the tricks in order to give correct scores for the players quickly. The article is in accordance with the judges manual and competition rules, its purpose is to make the judges have more clear mastery about the characters and difficulties of the tricks, therefore give more fairly and right scores for the performances of the players.